Consciência sanitária : uma questão de comunicação e saúde : um estudo a vigilância sanitária de Vitória - Franco, Fabiana Campos (2006)
The paper is a case study based on the critical analysis of the communication process used by the Sanitary Surveillance of Vitória, ES in the development of its functions and in the fulfillment of its mission of prevention, protection and recovery of the population's health. By applying structured questionnaires with open, semi-open and closed questions with industry officials and with a sample taken from the list of taxpayers who received the health permit in 2003 we made a diagnosis of existing communication problems and suggested possible changes. We chose to have as theoretical reference beyond critical theory, research conducted by the group of Latin American Communicational thinkers because their works are closer to the Brazilian reality. The results show that the communication for health still does not receive the necessary recognition in the daily activities aimed at collective health, in the case of victory. (AU)